Pengaruh Intellectual Capital, Profitabilitas, Dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Sektor Properti, Real Estate, Dan Konstruksi Bangunan Yang Terdaftar Di Bursa Efek Indonesia - Haryani Chandra; Hamfri Djajadikerta (Ultima Accounting : Jurnal Ilmu Akuntansi, 2017)
Go public companies have main purpose to increase firm value consistently. Increased firm value can reflect the increase in the prosperity of shareholders. The purpose of this research is to determine whether intellectual capital, profitability, and leverage have an influence on firm value. This research is expected to help companies to determine the focus on managing the factors those have an influence towards firm value and help investors and potential investors to make investment decisions. This research is conducted on firms listed in property, real estate, and building construction sector in Indonesia Stock Exchange during 2010 until 2015. Samples are selected by simple random sampling method. The research method used is the regression analysis. Intellectual capital is measured by value added intellectual coefficient (VAIC), profitability is measured by return on assets (ROA), leverage is measured by debt- to-equity ratio (DER), and firm value is measured by the year-end closing stock price. The results showed that intellectual capital, profitability, and leverage have partially a significant positive influence on firm value. In addition, intellectual capital, profitability, and leverage have significant influence simultaneously on firm value. Keywords: firm value, intellectual capital, leverage, profitability